Influence of initial wood moisture on decay process by two brown- rot fungi - Benítez, Valentina; Franco, Jorge; Camargo, Álvaro; Raimonda, Pablo; Mantero, Carlos; Ibáñez, Claudia (Maderas. Ciencia y Tecnología, 2021)
The biological decomposition of lignocellulosic materials caused by basidiomycetes plays an essential role in the carbon cycle. Brown rot fungi represent important agents in biodegradation of wood products and standing coniferous trees in natural ecosystems. The initial moisture content of the wood is an important factor in the degradation process. In this work, the effects of initial moisture content of Eucalyptus grandis sapwood on decay by two brown rot fungi Gloeophyllum trabeum and Laetiporus sulphureus were studied over a 10-month period. Fungal activity was evaluated, through wood weight loss, moisture content, anatomical changes (scan electronic and fluorescence microscopy) and Fourier-transform infrared spectroscopy. Weight loss increased through the 10-month test for both fungi, Laetiporus sulphureus producing higher mass losses. Colonization of the wood by both fungi started below the fiber saturation range. It was observed that the initial moisture content of the wood influenced the rate of deterioration: the wet samples showed higher weight loss compared to the dry samples. Changes in the chemical composition and structure of cell walls were detected. The initial moisture content of the substrate affected the development of the fungi, slowing their growth.